2017
DOI: 10.3177/jnsv.63.148
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping Analysis of Bitter-Taste Receptor Genes <i>TAS2R38</i> and <i>TAS2R46</i> in Japanese Patients with Gastrointestinal Cancers

Abstract: Summary Type-2 bitter-taste receptors (TAS2Rs) are important for the evaluation of food quality and the nutritional control in animals. Mutations in some TAS2Rs including TAS2R38 are known to increase susceptibility to various diseases. However, the involvement of TAS2Rs in cancers has not been well understood. We conducted a pilot study by genotyping two TAS2R genes, TAS2R38 and TAS2R46, in Japanese cancer patients diagnosed with the following types of cancer: biliary tract cancer, hepatocellular carcinoma, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 43 publications
1
35
1
Order By: Relevance
“…Epidemiological studies in multiple ethnicities were conducted to examine the association between the T2R38 bitterness receptor and cancer with genetic variation as a modifying factor. Increased risk for colorectal and GI cancer associated with the TAS2R38 AVI/AVI diplotype was observed in Germans and Japanese (3,20). A Korean study also showed that PAV/AVI increased the risk for GC (19).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Epidemiological studies in multiple ethnicities were conducted to examine the association between the T2R38 bitterness receptor and cancer with genetic variation as a modifying factor. Increased risk for colorectal and GI cancer associated with the TAS2R38 AVI/AVI diplotype was observed in Germans and Japanese (3,20). A Korean study also showed that PAV/AVI increased the risk for GC (19).…”
Section: Discussionmentioning
confidence: 98%
“…The studies were all designed for case-control investigations. Specifically, three and four studies were conducted in Caucasian (3,17) and Asian populations (17)(18)(19)(20), respectively. A single study was performed in a Polynesian (native Hawaiian) population (17).…”
Section: The Details Of the Analyzed Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…RNAseq failed to detect other TAS2Rs. Of note, TAS2R38 expression in the intestine is related to the risk of intestinal cancers associated with the taster/non-taster phenotype [10]. To confirm the expression pattern of TAS2R38 in the intestine, we performed RT-qPCR analyses of TAS2R38, GNAT3 (gustducin), and TRPM5 (Tables S2, S3 and Figure 2).…”
Section: Rnaseq and Rt-pcrmentioning
confidence: 99%
“…It has been found that non-tasters of PTC is more confused in the accuracy of taste compared to the tasters and this may lead to the infection of some diseases at sometimes [38]. Also, both alleles of the taster or non-taster of the PTC can contribute to the infection and the resistance of some diseases being the non-taster are the most susceptible [39] [40]. Timpson et al [21] pointed to the possibility of non-taster infected by heart disease and stroke more than tasters, but the results did not confirm this.…”
Section: Discussionmentioning
confidence: 99%